Output intensity of LED light curing units in dental offices of Piura, Peru - Crista Gadith Palacios Rivas; Dora Denisse Cruz Flores; Carmen Teresa Ibáñez Sevilla; MIGUEL ANGEL RUIZ-BARRUETO (Editorial Ciencias Médicas, 2022)
Introduction: Light curing lamps that use light-emitting diodes (LED) are used in dentistry for the polymeric conversion of dental restorative materials. It has been reported that inadequate light intensity in the lamp would not ensure the appropriate polymerization of restorative materials. Objective: Determine the output intensity of LED light curing units used in dental offices of the city of Piura, Peru, in the year 2020. Methods: An observational descriptive study was conducted. Measurements were taken of the light output of 70 LED light curing lamps using a radiometer with a wavelength of 400-500 nm and a light intensity measurement capacity of up to 3 500 mw/cm2. Intensity below 400 mw/cm2 was recorded as low, from 400 to 800 mw/cm2 as medium, from 800 a 1 200 mw/cm2 as high and above 1 200 mw/cm2 as very high. Results: Intensity was medium in 48.5% of the lamps analyzed, high in 22.86%, low in 15.71% and very high in 12.86%. A lower frequency of lamps with greater clinical use was reported. Conclusions: The LED light curing lamps used in dental offices of the province of Piura during the year 2020 emit an average output intensity of 778.14 mW/cm2, which corresponds to medium intensity.